EEN Yesterday and Today … CDED Today and Tomorrow - Herrador-López, Marta; Martin‐Masot, Rafael; Navas-López, Víctor Manuel (MDPI (Nutrients), 2020)
The treatment of Pediatric Crohn’s Disease (CD) requires attention both to achieve mucosal healing and to optimize growth, while also maintaining proper bone health. Exclusive Enteral Nutrition (EEN) is recommended as first-line treatment in luminal CD. The therapeutic mechanisms of EEN are being discovered by advances in the study of the gut microbiota. Although the total exclusion of a normal diet during the time of EEN continues to be of high importance, new modalities of dietary treatment suggest a successful future for the nutritional management of CD. In this sense, Crohn’s Disease Exclusion Diet (CDED) is a long-term strategy, it apparently acts on the mechanisms that influence the appearance of inflammation (reducing dietary exposure to products negatively affecting the microbiota), but does so using specific available whole foods to achieve this goal, increases the time of clinical remission and promotes healthy lifestyle habits. The development of CDED,which partly minimizes the problems of EEN, has enabled a turnaround in the treatment of pediatric CD. This review highlights the role of enteral nutrition in the treatment of Crohn’s disease with special emphasis on newer dietary modalities such as CDED.
Keywords: Alimentación enteral; Dieta en enfermedades; CDED; Crohn's disease; Adults; Children; Dietary treatment; Exclusive enteral nutrition; Treatment